The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1002/dvg.20266
|View full text |Cite
|
Sign up to set email alerts
|

Human CYP11A1 promoter drives Cre recombinase expression in the brain in addition to adrenals and gonads

Abstract: The first step of steroid biosynthesis is catalyzed by cytochrome P450scc, encoded by CYP11A1. To achieve steroidogenic tissue-specific inactivation of genes in vivo by the Cre-loxP approach, we used the 4.4-kb regulatory region of the human CYP11A1 gene to drive Cre recombinase expression in the tissues that produce steroids. The resulting SCC-Cre mice express high levels of Cre in the adrenal cortex and gonads at the same sites as that for the endogenous CYP11A1 expression. In addition, Cre activity was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Two published lines aimed at targeting steroidogenic cell lineages exhibit expression restricted to LCs within the testis (while also targeting steroidogenic organs outside of the testis such as adrenals). Use of 4.4 kb of the human Cyp11a1 promoter (which makes P 450 -SCC) has been exploited to make a SCC-iCre (Wu et al 2007). In addition to LC expression, the SCC-iCre is expressed in adrenals and the brain.…”
Section: Leydig Cellsmentioning
confidence: 99%
“…Two published lines aimed at targeting steroidogenic cell lineages exhibit expression restricted to LCs within the testis (while also targeting steroidogenic organs outside of the testis such as adrenals). Use of 4.4 kb of the human Cyp11a1 promoter (which makes P 450 -SCC) has been exploited to make a SCC-iCre (Wu et al 2007). In addition to LC expression, the SCC-iCre is expressed in adrenals and the brain.…”
Section: Leydig Cellsmentioning
confidence: 99%
“…Recent studies using a P450scc-cre reporter (Wu, et al, 2007) have shown that the P450scc promoter is expressed in the cortex, hippocampus, thalamus, hypothalamus (dorsomedial ventromedial hypothalamus and arcuate nucleus). We prepared P450c17-GFP transgenic mice, using a 1.5 kb promoter region of the rat P450c17 gene.…”
Section: Introductionmentioning
confidence: 99%
“…The plasmid pSCC4.4-iCreIn, which contains the 4.4-kb sequence of the human CYP11A1 promoter driving iCre gene, has been described previously (Wu et al, 2007). The transgene fragment containing 3.8 kb or 2.7 kb of CYP11A1 promoter region was generated by digestion of pSCC4.4-iCreIn with NheI and SalI, or BsrGI and SalI.…”
Section: Plasmid Constructsmentioning
confidence: 99%
“…The SCC-Cre transgenic mouse line generated previously (Wu et al, 2007) were mated with ROSA26 reporter mice to produce SCC-Cre/R26R double transgenic mice as described. To generate the transient SCC-Cre/R26R double transgenic embryos, purified transgenic DNA fragments were injected into the pronuclei of fertilized eggs derived from superovulated C57BL/6J female mated with homozygous male ROSA26 reporter mice.…”
Section: Generation Of Scc-cre/r26r Micementioning
confidence: 99%
See 1 more Smart Citation